2017
DOI: 10.1155/2017/5841814
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Improved Hippocampal Neurogenesis following Traumatic Brain Injury in Mice through Inhibition of TLR4 Signaling Pathway

Abstract: The protective role of electroacupuncture (EA) treatment in diverse neurological diseases such as ischemic stroke is well acknowledged. However, whether and how EA act on hippocampal neurogenesis following traumatic brain injury (TBI) remains poorly understood. This study aims to investigate the effect of EA on hippocampal neurogenesis and neurological functions, as well as its underlying association with toll-like receptor 4 (TLR4) signaling in TBI mice. BrdU/NeuN immunofluorescence was performed to label new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Studies have reported that TLR4 in the central nervous system (CNS) involved in memory, learning impairment [10] and cognitive decline [11]. Recently, TLR4 was also identified as a modulator of neurogenesis in the brain during injuries, cerebral ischemia, and cognitive decline [12], and it is recognized to contribute to neuroplasticity [13]. Studies demonstrated that cognitive dysfunction was alleviated possibly by inhibiting hippocampal TLR4 activation in aged rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that TLR4 in the central nervous system (CNS) involved in memory, learning impairment [10] and cognitive decline [11]. Recently, TLR4 was also identified as a modulator of neurogenesis in the brain during injuries, cerebral ischemia, and cognitive decline [12], and it is recognized to contribute to neuroplasticity [13]. Studies demonstrated that cognitive dysfunction was alleviated possibly by inhibiting hippocampal TLR4 activation in aged rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, TLR4/MyD88/MAPK/NF-κB signal pathway was one of the classical pathways in ischemic stroke‑induced inflammation. Many drugs [ 50 , 51 ] and treatments [ 52 ] could inhibit the TLR4-mediated inflammatory responses and decrease proinflammatory cytokine release through the MyD88-dependent signaling pathway. MyD88-dependent signaling contributes to the inflammatory responses induced by cerebral ischemia/reperfusion [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These treatments were able to alleviate the nerve damage and promote neurological recovery after TBI. Electro-acupuncture-induced TLR4 signaling inhibition has been used to promote hippocampal neurogenesis and neurological recovery post-trauma [ 58 ].…”
Section: Discussionmentioning
confidence: 99%